(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The article explores the impact of four different parenting styles – authoritative, authoritarian, permissive, and uninvolved – on children’s academic performance. It examines the characteristics of each approach and the potential impact of parenting styles on children’s mental health, academic motivation, self-esteem, and socio-emotional development. The article provides evidence from research to support the argument that authoritative parenting, characterized by warmth, responsiveness, and clear expectations, tends to have the most positive impact on children’s academic outcomes. It also discusses the potential long-term impact of parenting styles on career success and overall wellbeing. The article concludes by highlighting the importance of positive parenting practices, highlighting ways that parents, teachers, and policymakers can support children’s academic and socio-emotional development.